The Role of Syariah Banking in Strengthening Micro, Small and Medium Enterprises (MSME) in Indonesia - Serlika Aprita; Erisa Ardika Prasada (International Journal of Global Sustainable Research, 2023)
Islamic banks have the opportunity to realize the government's expectations as stated in the policy of regulatory changes with the priority of cooperatives, micro, small and medium entrepreneurs or the people's economic system that provides opportunities to all levels of society without discrimination. The axiological content that underlies the operation of Islamic banks is also a separate force in efforts to develop the overall economy of the community. This research aims to examine the role of Islamic banking as a social institution in strengthening micro, small and medium enterprises (MSME or known as UMKM in Indonesia). The type of legal research used in this legal writing is normative legal research with a statutory approach. The statutory approach is carried out by examining all laws and regulations related to the role of Islamic banking in strengthening MSMEs.  The results of the research found that Islamic banking must be able to act as a social institution in addition to being a commercial institution. Acting as a social institution that can maximally improve the economy of MSMEs through al-qardh and al-qardh al-hasan financing. Both of these financing models are based on non-profit lending contracts.